ANALISIS POTENSI PENDAPATAN PELAKU UMKM DI DESA TRITIH WETAN PASCA PANDEMI - Charisma Fatimah Azzahro; Loka Valmilatul Prayuga (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are the biggest pillar of the country's economy. This is in accordance with data that there are 64.2 million domestic MSME actors. However, during the pandemic, the Indonesian economy declined, including the income of MSME actors. This study aims to find out what changes have occurred during the pandemic to MSME actors. So, what are the implications of these changes? This study uses a sample of MSME actors in the Gelora Jaya field, Tritih Wetan Village. The results of this study, namely all MSME actors who were used as research samples, experienced a decrease in income of at least 50% for one year.